Detection of unstable plaque phantom by ultrasonic velocity-change imaging method under cold exposure. (30th May 2018) - Kumagai, Yuta; Aotani, Yuhei; Kameda, Masanobu; Wada, Kenji; Matsunaka, Toshiyuki; Horinaka, Hiromichi
Abstract: We have investigated the ultrasonic velocity-change (UVC) imaging method to detect unstable vessel plaques using the difference in the temperature coefficient of ultrasonic velocity between water and fat. Thus far, to obtain effective ultrasonic velocity changes in the UVC imaging method, a warming procedure using a laser or an ultrasonic wave has been used. In this study, we utilize a cooling procedure instead of the warming procedure for this imaging method. As a result, lipid areas inside a carotid artery phantom were more clearly identified in the UVC image obtained under cold exposure.